Volume 1: Turbomachinery 1996
DOI: 10.1115/96-gt-166
|View full text |Cite
|
Sign up to set email alerts
|

Measurements in a Transitional Boundary Layer With Görtler Vortices

Abstract: The laminar-turbulent transition process has been documented in a concave-wall boundary layer subject to low (0.6%) free-stream turbulence intensity. Transition began at a Reynolds number, Rex (based on distance from the leading edge of the test wall), of 3.5×105 and was completed by 4.7×105. The transition was strongly influenced by the presence of stationary, streamwise, Görtler vortices. Transition under similar conditions has been documented in previous studies, but because concave-wall transition tends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…29 A tilting of the vortices that causes a local rise in intermittency above the near wall values is suspected to be the cause of the inflection point in the mean velocity profile and seems to be the source of turbulence production. 38 Volino and Simon 38 suggested that the instability which causes the tilting of the Görtler vortices by producing a region of high mean velocity gradient near the inflection point may be driving the transition process in this flow.…”
Section: Resultsmentioning
confidence: 98%
“…29 A tilting of the vortices that causes a local rise in intermittency above the near wall values is suspected to be the cause of the inflection point in the mean velocity profile and seems to be the source of turbulence production. 38 Volino and Simon 38 suggested that the instability which causes the tilting of the Görtler vortices by producing a region of high mean velocity gradient near the inflection point may be driving the transition process in this flow.…”
Section: Resultsmentioning
confidence: 98%
“…In order to take a fundamental look at turbomachinery transition, recent experiments have been conducted in somewhat simplified geometries which represent certain aspects of the low‐pressure turbine flows. These include the works of Blair40, Baughn et al 41, Qiu & Simon42, Simon et al 43, Sohn et al 44, Murawski et al 45, Jonas46, Funazaki & Kitazawa47, Matsubara et al 48, Boyle et al 49, Volino & Simon50–52, Boyle & Simon53, Volino & Hultgren54, Hatman & Wang55,56, Chakka & Schobeiri57, Funazaki et al 58,59 and Schobeiri et al 60. The Volino & Simon study was on a curved surface with various pressure gradients imposed.…”
Section: Classical Transition Research and The Low‐pressure Turbinementioning
confidence: 99%
“…At the second peak, more inflection point is found, that is, at approximately y = 0.6 mm. The more inflection points seem to trigger the breakdown of vortex structures [28]. Figure 6(c) shows that the maximum growth of disturbance amplitude ߢ ௨,௫ decreases at the flat entrance plate before slightly increases towards the first peak and decreases once more as the flow moves further downstream.…”
Section: Resultsmentioning
confidence: 93%